In Situ Measurement Methods for the CO(2)-Induced Gelation of Biopolymer Systems - Preibisch, Imke (Gels, 2020)
This work presents two novel methods to investigate in situ the carbon dioxide (CO(2))-induced gelation of biopolymer-based solutions. The CO(2)-induced gelation is performed in a viewing cell at room temperature under CO(2) pressure (20 to 60 bar), whereby calcium precursors are used as cross-linkers. The novel methods allow the in situ optical observation and evaluation of the gelation process via the change in turbidity due to dissolution of dispersed calcium carbonate (CaCO(3)) particles and in situ pH measurements. The combination of both methods enables the determination of the gelation direction, gelation rate, and the pH value in spatial and temporal resolution. The optical gelation front and pH front both propagate equally from top to bottom through the sample solutions, indicating a direct link between a decrease in the pH value and the dissolution of the CaCO(3) particles. Close-to-vertical movement of both gelation front and pH front suggests almost one dimensional diffusion of CO(2) from the contact surface (gel–CO(2)) to the bottom of the sample. The gelation rate increases with the increase in CO(2) pressure. However, the increase in solution viscosity and the formation of a gel layer result in a strong decrease in the gelation rate due to a hindrance of CO(2) diffusion. Released carbonate ions from CaCO(3) dissolution directly influence the reaction equilibrium between CO(2) and water and therefore the change in pH value of the solution. Increasing the CaCO(3) concentrations up to the solubility results in lower gelation rates.